Fusarium infections: Epidemiological aspects over 10 years in a university hospital in France - Benoît Thomas; Nelly Contet Audonneau; Marie Machouart; Anne Debourgogne (Elsevier, 2020)
Background: Fusarium is an environmental mold that causes deep or superficial mycosis in immunocompromised or immunocompetent patients respectively. Methods: This epidemiological study evaluated the frequency of Fusarium infections in our university hospital center in France over a decade from 2007 to 2016 and its representativeness in the main clinical infections. Results: A total of 715 Fusarium sp. were isolated from various sampling sites. Fusarium was detected in 0.47% of blood cultures, 31.1% of ophthalmic samples, and 8.48% of nail samples. The frequency of Fusarium infections was stable over this decade. Conclusions: The main Fusarium species complexes recorded in this study were Fusarium oxysporum species complex and Fusarium solani species complex, indicating the importance of Fusarium as a fungal agent that should be considered in clinical practice. A focus on invasive fusarioses shows that they all occur in hematology patients.